Associations between challenging parenting behavior and creative tendencies of children: the chain mediating roles of positive emotion and creative self-efficacy - Shi, Dasheng; Wang, Yidi; Jin, Ruining; Chu, Lin (Frontiers in Psychology, 2024)
Parenting behavior has been reported to be closely associated with children's creativity, yet the association between challenging parenting behavior and children's creative tendencies, as well as the potential mechanisms connecting the two, remains ambiguous. Based on the Social Cognitive Theory and the Self-efficacy Theory, the research aims to examine the correlation between Chinese parents' challenging parenting behaviors and their children's creative tendencies, as well as the chain mediating role of children's positive emotions and creative self-efficacy. In total, 2647 families were surveyed with questionnaires completed by parents on the Challenging Parenting Behaviors Scale and by children on the Positive/Negative Emotions Scale, the Creative Self-efficacy Scale, and the Williams Creative Tendency Test Scale, and analyzed using structural equation modeling (SEM) in SPSS 22.0 and Mplus 8.3. The findings indicate that challenging parenting behavior has a positive correlation with children's positive emotions, creative self-efficacy, and creative tendencies. Through positive emotions, creative self-efficacy, and a chain mediated pathway between these two variables, challenging parenting behaviors increase children's creative tendencies. In summary, this investigation further explains the interactions between challenging parenting behavior and children's creative tendencies, discusses the implications for future research on children's creative tendencies, and expends the theoretical foundation of parenting styles and children's creativity. In practice, this suggests that parents can enhance their children's creative tendencies and abilities by adopting appropriate challenging parenting behaviors.